2021
DOI: 10.1016/j.foodchem.2020.128154
|View full text |Cite
|
Sign up to set email alerts
|

Higher microbial diversity in raw than in pasteurized milk Raclette-type cheese enhances peptide and metabolite diversity after in vitro digestion

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Cheese digestibility is different from that of milk and individual caseins or whey proteins; although the chemical composition of the protein is the same, the cheese structure is more complex. Cheese microstructure and texture have been shown to influence the rate of milk protein hydrolysis [ 33 , 34 ]. During cheese making, coagulation of the casein micelles is achieved by the enzymatic (chymosin) hydrolysis of k-casein and caseins, which are heat stable both as casein micelles and in the form of caseinates.…”
Section: Resultsmentioning
confidence: 99%
“…Cheese digestibility is different from that of milk and individual caseins or whey proteins; although the chemical composition of the protein is the same, the cheese structure is more complex. Cheese microstructure and texture have been shown to influence the rate of milk protein hydrolysis [ 33 , 34 ]. During cheese making, coagulation of the casein micelles is achieved by the enzymatic (chymosin) hydrolysis of k-casein and caseins, which are heat stable both as casein micelles and in the form of caseinates.…”
Section: Resultsmentioning
confidence: 99%
“…lactis , L. plantarum/pentosus and Weissella paramesenteroides , with a relative abundance of Lc. lactis exceeding 50% [ 29 ]. In the present study W. paramesenteroides was also detected in five samples with a low abundance (<0.085%).…”
Section: Resultsmentioning
confidence: 99%
“…To understand better the changes that occur in the bioactive peptides profile during gastrointestinal digestion of cheeses, several studies were performed using static and dynamic models that simulate the gastrointestinal digestion in vitro 17–22,35,71 . Despite the changes in peptide profiles during the digestion and the hydrolysis of some bioactive sequences, studies have shown the bioactive potential of cheeses after digestion and potential intestinal absorption of some bioactive fragments.…”
Section: Effect Of Gastrointestinal Digestion On Cheese‐derived Bioactive Peptides’ Stability and Releasementioning
confidence: 99%